History medicine in Britain, crime and punishment in Britain, Anglo-Saxon and Norman England, early Elizabethan England - Walsh, Ben (Hodder Education, 2022)
Exam board: Pearson Edexcel Level: GCSE (9-1) Subject: History First teaching: September 2016 First exams: Summer 2018 Endorsed for Pearson Edexcel qualifications Discover a fresh approach to Pearson Edexcel GCSE History, developed by bestselling author Ben Walsh while working with hundreds of students and teachers across England. Unlike other textbooks, which were written before the 9-1 GCSEs had been taught, this book is rooted in real classroom experience, so it tackles the big challenges head on. You can rely on Ben Walsh History to: > Do the hard work for you. The large amount of content has been turned into a manageable and logically structured GCSE course, which teachers and students can easily follow in the time available > Use good history practice as the vehicle for exam success. This book doesn't just teach to the test; it progressively builds students' skills and conceptual understanding, turning them into accomplished historians who will approach their exams with confidence > Hook students in and make history memorable. Ben's trademark mix of rich narrative and interesting sources will engage students of all abilities and provide suitable challenge to move them up the grades > Focus on what really matters. All of the features in the book are designed to help students to consolidate their knowledge and remember the key content - from 'Focus tasks' and regular 'Retrieval practice' questions to end-of-chapter revision tasks > Give straightforward exam advice. 'What does it mean?', 'Jargon buster' and 'Myth buster' boxes explain the exam requirements and question types. 'Top tips', 'Success criteria', annotated model answers and simplified 'thumbs up' mark schemes ensure that students understand how to answer questions effectively This book covers the following units: Thematic study and historic environment > Medicine in Britain,